2021
DOI: 10.1080/1351847x.2021.1989008
|View full text |Cite
|
Sign up to set email alerts
|

Investor attention and idiosyncratic risk in cryptocurrency markets

Abstract: We explore the impact of investor attention on idiosyncratic risk in the cryptocurrency markets. Taking the Google Trends Index as the measure of investor attention, we find that investor attention can significantly reduce cryptocurrencies' idiosyncratic risks by increasing the liquidity. We further study possible cross-sectional variations of the effect of investor attention on idiosyncratic risk. Evidence shows that the investor attention effect is more pronounced for smaller-cap and younger cryptocurrencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…To improve the reliability of the analysis, we follow prior literature and reconstruct Google Trends data, which can be downloaded for a maximum of 270 days. To create a complete time series of daily data for a longer period, we adopted the overlapping period strategy suggested by Bleher and Dimpfl (2018), which is a common methodology in finance literature (Enoksen et al 2020;Yao et al 2021). We downloaded two sets of 270 days of daily data and used 115 days as an overlapping period to rescale the Google Trends data to obtain one complete time-series data for each cryptocurrency.…”
Section: Robustness Analysismentioning
confidence: 99%
“…To improve the reliability of the analysis, we follow prior literature and reconstruct Google Trends data, which can be downloaded for a maximum of 270 days. To create a complete time series of daily data for a longer period, we adopted the overlapping period strategy suggested by Bleher and Dimpfl (2018), which is a common methodology in finance literature (Enoksen et al 2020;Yao et al 2021). We downloaded two sets of 270 days of daily data and used 115 days as an overlapping period to rescale the Google Trends data to obtain one complete time-series data for each cryptocurrency.…”
Section: Robustness Analysismentioning
confidence: 99%
“…Recently, many studies have shown that investor attention has a significant impact on the cryptocurrency markets, including returns (Dastgir et al, 2019;Liu & Tsyvinski, 2021;Philippas et al, 2019;Subramaniam & Chakraborty, 2020;Zhang & Wang, 2020), price discovery (Ibikunle et al, 2020), and volatility (Sabah, 2020;Yao et al, 2021a;Zhang & Wang, 2020). However, little research has focused on the relationship between investor attention and cryptocurrency market liquidity as well as the role of investor attention in different market states.…”
Section: Introductionmentioning
confidence: 99%